IDENTIFIKASI FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKTIVITAS SDM (STUDI KASUS PADA KARYAWAN BANK BTN SYARIAH MALANG) - Alif Dwi Amarsyah (Jurnal Ilmiah Mahasiswa FEB, 2019)
ABSTRACTThis study aims to identify the influence of knowledge, skills, abilities, attitudes and behaviors on HR productivity of Bank BTN Syariah Malang. The number of samples in this studywere 90 respondents from 116 employees. The sampling technique uses proportional randomsampling, which is to consider the elements or categories in the population to be sampled. Thedata collection method used a questionnaire and documentation. The data analysis method usedis descriptive statistics and multiple linear regression.The results of this study indicate that (1) Knowledge has a significant effect on HRproductivity of Bank BTN Syariah Malang, (2) Skills have a significant effect on HR productivityof Bank BTN Syariah Malang, (3) Abilities have a significant effect on HR productivity of BankBTN Syariah Malang, (4) Attitudes has a significant effect on HR productivity of Bank BTNSyariah Malang and (5) Behaviors has a significant effect on HR productivity of Bank BTNSyariah Malang.Keywords: Knowledge, Skills, Abilities, Attitudes, Behaviors and Productivity.